An Analysis of the Categories of English Words and Phrases Used in Selected Hausa Home Videos - Suleiman , Muhammad Tanko (International Journal of Arts, Languages, Linguistics and Literary Studies, 2024)
This paper examines the presence and usage of English words and phrases in selected Hausa home videos titled: Zuri’a (Family, 2012), and (La miraj (The Barren, 2013). Hausa is an Afro-asiatic language spoken by millions of people across West Africa and the Sahel region. It is one of the most widely spoken languages in the region and is also lingua franca of West Africa. The purpose of this study is to analyze two selected Hausa home videos, identify and categorize the English words and phrases used in the videos. The study utilized a qualitative research approach to analyze the selected home videos. The data collected was analyzed by coding the English words and phrases according to a descriptive classification system. The study identified a number of expressions which were code-mixed in Hausa and English. These were extracted and used as data, and subsequently some native speakers and Hausa translators were involved in the editing of the data. The study also discovered that the English words and phrases used in Hausa home videos were heavily influenced by the political, social, administrative and cultural lifestyle of the region which is reflective of the values and norms of the Hausa society. Overall, this study provides an overview of the categories of English words and phrases used in selected Hausa home videos. The findings from the study can be used to improve English language education in the region, as well as gain a better understanding of the Hausa language and its influence on English.